Staged Folklore : The National Folk Theatre of Ireland 1968-1998 - O'Connell, John; Motherway, Susan H. (Book collections on Project MUSE., 2022)
"This book concerns the foundation and development of the National Folk Theatre of Ireland, which has recently celebrated 50 years of performances. Also called 'Siamsa Tíre', it examines the ways in which the Theatre provides a locus for promoting and transmitting customary knowledge that had become lost due to modernisation and urbanisation. It also interrogates critically the role of the Theatre in presenting and representing local traditions to non-local audiences, tourism being a key component in the sustainable continuation of expressive culture"--